The Protein Quality Control Network in Caulobacter crescentus - Schroeder, Kristen; Jonas, Kristina (Frontiers in Molecular Biosciences, 2021)
The asymmetric life cycle of Caulobacter crescentus has provided a model in which to study how protein quality control networks interface with cell cycle and developmental processes, and how the functions of these systems change during exposure to stress. As in most bacteria, the protein quality control network of Caulobacter contains highly conserved ATP-dependent chaperones and proteases as well as more specialized holdases. During growth in optimal conditions, these systems support a regulated circuit of protein synthesis and degradation that drives cell differentiation and cell cycle progression. When stress conditions threaten the proteome, most components of the Caulobacter proteostasis network are upregulated and switch to survival functions that prevent, revert, and remove protein damage, while simultaneously pausing the cell cycle in order to regain protein homeostasis. The specialized physiology of Caulobacter influences how it copes with proteotoxic stress, such as in the global management of damaged proteins during recovery as well as in cell type-specific stress responses. Our mini-review highlights the discoveries that have been made in how Caulobacter utilizes its protein quality control network for regulating its life cycle under optimal and proteotoxic stress conditions, and discusses open research questions in this model.